Pengaruh Guru Profesional dan Iklim Sekolah Terhadap Mutu Pembelajaran SD Muhammadiyah Terpadu Ponorogo - Philip Fatma Dewi (Muslim Heritage, 2017)
Abstract: This research aims to determine (1) the effect of professional teacher on the quality of learning, (2) the effect of school climate on the quality of learning, (3) the effect of teacher professional and school climate on the quality of learning. This research employed quantitative approach and the research design was Expost_Facto. The results of this study indicate: (1) There is a positive and significant effect of professional teachers on the quality of learning as it is proved by ttest 15.368> ttable 1.98 with the coefficient of determination 0.7. (2) There is a positive and significant effect of school climate on the quality of learning which is shown by ttest 22,745> ttable 1,98 with coefficient of determination 0,837. (3) There is a positive and significant effect of  teacher professional and school climate on the quality of learning shown by Ftest 257,963> Ftable 3,09 with contribution effectiveness equal to 83,8%. It can concluded that professional teachers and school climate significantly influence the quality of learning. Therefore, it is suggested that teachers should keep on improving their professionalism through sustainable professional development activities. Then, schools and stakeholders should establish a good school climate through the establishing and good school culture. Furthermore, the government should improve the continuous professional development activities for teachers. As for other researchers should conduct further research to reveal other factors that affect the less maximum quality of learning.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh guru profesional terhadap mutu pembelajaran, pengaruh iklim sekolah terhadap mutu pembelajaran, dan pengaruh secara bersama-sama antara guru profesional dan iklim sekolah terhadap mutu pembelajaran. Penelitian ini menggunakan pendekatan kuantitatif, dengan rancangan penelitian Expost_Facto. Hasil penelitian ini menunjukkan terdapat pengaruh yang positif dan signifikan guru profesional terhadap mutu pembelajaran yang ditunjukkan dengan thitung 15,368 > ttabel 1,98 dengan koefisien determinasi 0,7, terdapat pengaruh yang positif dan signifikan iklim sekolah terhadap mutu pembelajaran yang ditunjukkan dengan thitung 22,745 > ttabel 1,98 dengan koefisien determinasi 0,837, dan terdapat pengaruh yang positif dan signifikan secara bersama-sama antara guru professional dan iklim sekolah terhadap mutu pembelajaran yang ditunjukkan dengan Fhitung 257,963 > Ftabel 3,09 dengan sumbangan efektifitas sebesar 83,8%. Penelitian ini menyimpulkan bahwa guru profesional dan iklim sekolah mempunyai pengaruh terhadap mutu pembelajaran. Oleh karena itu disarankan kepada para guru hendaknya terus berusaha meningkatkan keprofesionalannya melalui kegiatan pengembangan keprofesian berkelanjutan. Bagi sekolah hendaknya membangun iklim sekolah yang baik melalui penanaman dan pembiasaan budaya sekolah yang baik oleh seluruh stakeholder sekolah. Bagi pemerintah hendaknya meningkatkan kegiatan pengembangan keprofesian berkelanjutan bagi guru. Sedangkan bagi peneliti lain hendaknya melakukan penelitian lebih lanjut guna mengungkap faktor-faktor lain yang mempengaruhi dan menyebabkan kurang maksimalnya mutu pembelajaran.